The Relationship between Emotional Intelligence (EQ) and Quarter Life Crisis in Final Year Students - Inayati, Syifa; Yuliana; Nasution, Riska Amalya (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Quarter life crisis is a crisis that occurs in early adulthood characterized by the appearance of emotional instability. The beginning of a quarter life crisis occurs when an early adult individual becomes a final year student who does not have enough preparation to face the realities of the world. Final year students need to have the ability to overcome these emotional instability. One of them is by having emotional intelligence (EQ) which can form a positive force to maintain harmony within oneself. This study aims to determine the relationship between emotional intelligence (EQ) and quarter life crisis in final year students of the Faculty of Medicine and Health Sciences, Jambi University. This research is a quantitative study that has used correlational methods with cross-sectional design. The sampling technique has used Proportionate Stratified Random Sampling with research instruments in the form of questionnaires in the form of SEIS and a quarter life crisis scale. Data analysis using univariate analysis and bivariate analysis with gamma correlation test. There is a significant relationship between emotional intelligence (EQ) and quarter life crisis in final year students of the Faculty of Medicine and Health Sciences, University of Jambi. The emotional intelligence (EQ) variable has a negative relationship with the quarter life crisis variable in final year students of the Faculty of Medicine and Health Sciences, University of Jambi. The lower the emotional intelligence (EQ), the higher the quarter life crisis and vice versa. Final year students are expected to improve emotional intelligence (EQ) as an adaptive coping mechanism to deal with quarter life crisis.